WHY REDDIT? HISTORIES, ETHICS, POLITICS & PRACTICES AS REDDIT TURNS 20 - Vilkins, Samantha; Carlon, Dominique; Nagappa , Ashwin; Stillman, Ari; Dehghan, Ehsan; Kasianenko, Kateryna; Suresh, Vish Padinjaredath; Bruns, Axel; Svegaard, Sebastian S.K.; Fitzgerald, Katherine (AoIR Selected Papers of Internet Research, 2026)
As Reddit approaches its twentieth anniversary in 2025, it occupies a unique and relatively under-studied place in the online landscape. The ruptures of recent internet history are visible as geological fixtures through the persistence and growth of structures and communities on Reddit. Once the self-proclaimed “front page of the internet”, to the latest tagline encouraging users to “dive into anything”, Reddit has evolved from a news alert homepage to a complex content ecosystem of over 3.5 million communities, each with distinct cultures, governance structures and communicative practices. Perhaps for this reason, Reddit has been extensively scraped for AI training material, leading to unintended results, such as the now-famous glue on pizza suggestion (McMahon & Kleinman, 2024). Reddit’s infrastructure remains semi-open with a monetized API, which places some restrictions on research as well as scraping/crawling. Nor is all content directly human-generated, as bots play a central role both in the platform’s governance, administration of separate subreddits, and user interactions. Reddit has recently seen all-time records in traffic and growth in research interest, particularly for studies of community dynamics, but in everything that has made the internet the internet, from fan groups to radicalization and back. Our panel celebrates the platform’s anniversary year and explores Reddit’s rising position as both subject and site of methodological, ethical, and political ruptures in internet research through five complementary papers. The first paper provides a historical examination of Reddit’s evolution over two decades, from a single landing page to a vast network of communities. This perspective identifies key moments of rupture in Reddit’s development, particularly its decision to enable user-created communities in 2008 – a move that fundamentally transformed its architecture and governance. The paper analyzes how competing analogies for Reddit’s identity, such as “city-state” versus “convention center”, reflect ongoing tensions between community autonomy and corporate control. Recent decisions to monetize its API and licence user data for AI training have created new conflicts and controversies, yet Reddit’s distinctive architecture has allowed it to maintain forms of resistance not possible on more centralized platforms. The second paper explores the ethical questions created by researching Reddit in what has become known as the post-API era. As platforms increasingly restrict access to user data, researchers face new challenges in collecting and analyzing social media content. This paper situates Reddit data collection within broader platform politics, arguing that researchers must shift from traditional ethical frameworks that have been shaped by corporate interests rather than user protection or desires. The paper calls for researchers to rise to the occasion, acting with utmost morality and looking to explicitly anti-capitalist modes of data ethics. The third paper examines political communication on Reddit and works with the concept of ‘sedimented polarization’ – a condition in which political fragmentation has become embedded in the platform’s architecture. Through mixed-methods analysis of political subreddits, this research identifies how Reddit’s structure shapes political discourses, with minimal cross-ideological interaction even on subreddits designed for diverse debate. Each political community develops distinctive communicative practices, information sources, and collective identities, often viewing other subreddits as antagonistic even when they share similar ideological orientations. This paper demonstrates how platform affordances, moderation practices, and user behaviors combine to create polarized environments. The fourth paper builds on this analysis by exploring toxic masculine practices on Reddit through a novel methodological framework. It develops a power-centric approach to online radicalization, examining how Reddit’s architecture enables the formation of “parasitic publics" that exert discursive violence upon marginalized groups. By applying specific computational techniques to analyze interactional data from various subreddits, this paper shifts how we understand and study radicalization online. Rather than focusing on content alone, it examines the communicative practices and power dynamics that shape interactions between dominant and marginalized communities on the platform. The fifth and final paper extends these investigations of community practices and ideological cleavages to a case study of fan communities, focusing on the ruptures and reformations in Taylor Swift related discussion on Reddit. The paper presents an adaptation of practice mapping, originally developed on X and Facebook data, to Reddit’s unique environment, capturing how users engage across multiple communities with varying norms. This research demonstrates how Reddit’s architecture enables both specialized community formation and complex cross-community practices, revealing patterns of engagement both invisible to traditional network analysis and made clearer by Reddit’s architecture itself. By examining Reddit’s past, present and future, this panel contributes to our understanding of contemporary platform politics by highlighting how Reddit’s unique architecture has grown, reacting to and shaping ruptures in conventional platform evolution narratives. As the platform navigates competing pressures of commercialization, content moderation, and community autonomy, it continues to occupy a distinctive position in the online landscape – neither fully succumbing to corporate logics nor entirely resisting them.